Production and Selection of Quality Protein Popcorn Hybrids Using a Novel Ranking System and Combining Ability Estimates - Parsons, Leandra; Ren, Ying; Yobi, Abou; Hurst, Preston; Angelovici, Ruthie; Rodriguez, Oscar; Holding, David R. (Frontiers in Plant Science, 2020)
Popcorn varieties are agronomically sub-optimal and genetically limited compared to other maize subspecies. To increase genetic diversity and improve popcorn agronomics, dent germplasm has been introduced to popcorn with limited success and generally, major loss of popping. Between 2013 and 2018, twelve Quality Protein Popcorn (QPP) inbreds containing Quality Protein Maize (QPM) and popcorn germplasm were produced that maintained popping while carrying the opaque-2 allele conferring elevated kernel lysine. This is an opportune trait in the growing market for healthier snacks and a model for mining QPM traits into popcorn. We crossed QPP inbreds to explore the effects of heterosis on popcorn protein, popping quality, and plant agronomics and selected hybrids for further production. To rank and intermediately prescreen hybrids, we utilized a novel hybrid-ranking model adapted from a rank summation index while examining the inbred general combining ability and hybrid specific combining ability estimates for all traits. We observed a biological manifestation of heterosis by categorizing hybrids by pedigree that resulted in a stepwise progression of trait improvement. These results corroborated our hybrid selection and offered insight in basic heterosis research. Estimates for popcorn quality and agronomic trait covariances also suggest the synergistic introgression of highly vitreous dent maize (QPM) into popcorn, providing a likely explanation for the successfully maintained vitreous endosperm, protein quality and popping traits in line with a remodeled proteome. QPP hybrids maintained improved amino acid profiles although different popping methods variably affected popcorn’s protein bound and free amino acid levels. This preliminary screening of QPP hybrids is enabling further quantitative selection for large-scale, complex trait comparison to currently marketed elite popcorn varieties.